PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS X IPA SMAN 7 PADANG - AULIA SABRINA (Jurnal Edukasi dan Penelitian Matematika, 2020)
One of the expected of mathematics learning in senior high schools is that students able to understanding mathematical concepts. But according to the result of the tests, the understanding of mathematical concepts of student in class X IPA of SMAN 7 Padang is still can be improve. This is happen because learning model used in schools have not facilitated students to improve their own capability to understanding of mathematical concept. One effort that can be offer to these problems is to apply cooperative learning model type Team Assisted Individualization. The type of this research is quasy-experiment, research design with The Nonequivalent Posttest-Only Control Group Design. Based on results of test and quizzed, it was concluded that understanding the mathematical concepts of students learning after applying cooperative learning model type Team Assisted Individualization  is better than understanding mathematical concepts of students learning by direct learning in class X IPA SMAN 7 Padang. Then, the development of students understanding mathematical concept during appling cooperative learning model type Team Assisted Individualization has increased. Keywords – Cooperative learning model, Team Assisted Individualization, understanding of mathematical concept